DAMPAK PERANG RUSIA-UKRAINA TERHADAP PEREKONOMIAN INDONESIA: ANALISIS VOLUME PERDAGANGAN DAN PERUBAHAN POLA PERDAGANGAN - Banurea, Poltak Parulian; Aini, Riza; Manurung, Harris (JOURNAL OF BUSINESS STUDIES, 2023)
This study aims to analyze the impact of the war between Russia and Ukraine and its implications for the Indonesian economy. The conflict between these two countries has affected Indonesia as a developing country connected to international trade networks. This research uses secondary data analysis methods based on media reports, policy analysis, and recent economic data. The factors analyzed include international trade, commodity prices, foreign investment, tourism sector, and financial market stability. The results showed that the war between Russia and Ukraine had a significant impact on the Indonesian economy. The direct impacts include a decrease in exports and imports, especially in terms of trade with Russia and Ukraine. In addition, commodity prices such as oil and natural gas also experienced significant fluctuations due to global market uncertainty. The indirect implications involve foreign direct investment (FDI) which could be affected by geopolitical instability. The tourism sector can also be negatively impacted, due to negative perceptions of security and stability in the region. The government can take appropriate measures to deal with such impacts, such as diversifying trade with other countries, strengthening domestic investment, and developing more self-reliant economic sectors.